Challenges and potential solutions in the development of COVID-19 pandemic control measures. (March 2021) - Azizi, H.; Esmaeili, E. Davtalab
Abstract: The coronavirus disease 2019 pandemic has become an unprecedented and major health concern all over the world. We discuss potential solutions and feasible strategies to reduce spread of infection and to develop disease control measures.